Teacher as the basis of competitiveness of technical university’s graduates - Бондаренко, В. В. (Scientific notes of the pedagogical department, 2018)
The article deals with one of the topical problems of training competitive graduates of technical universities in Ukraine. The author offers a solution to the problem stated by means of improving and optimizing the teaching staff activity. The new educational space, which has long transcended national borders, is of large number of problems related to the quality of education, definition of its tasks and objectives, its content and structure. Without solving these problems, no one can speak of the professional competence of professional and higher educational institutions’ graduates. The quality control of the teaching staff of the higher technical educational institution is closely related to the fundamental changes in requirements in the competitive market of educational services. It is the market relations that lead to a significant increase in the requirements for professional skills and qualification level of university graduates. High professional training is the factor that ensures the socialization and real entry of the university graduate into the conditions of a real competitive environment and his social protection. Improving the quality of the technical universities’ functioning in Ukraine provides that teachers resulting from basic values and using the necessary abilities make their daily activities on the principle of continuous improvement taking into account the mission, objectives, goals and strategies of the higher technical educational institution.